The traditional Chinese medicine and non-small cell lung cancer: from a gut microbiome perspective - Wang, Xuelin; Hou, Liming; Cui, Meng; Liu, Junnan; Wang, Mengzhou; Xie, Jianwu (Frontiers in Cellular and Infection Microbiology, 2023)
Non-small cell lung cancer (NSCLC) is one of the most serious diseases affecting human health today, and current research is focusing on gut flora. There is a correlation between intestinal flora imbalance and lung cancer, but the specific mechanism is not clear. Based on the “lung and large intestine being interior-exteriorly related” and the “lung-intestinal axis” theory. Here, based on the theoretical comparisons of Chinese and western medicine, we summarized the regulation of intestinal flora in NSCLC by active ingredients of traditional Chinese medicine and Chinese herbal compounds and their intervention effects, which is conducive to providing new strategies and ideas for clinical prevention and treatment of NSCLC.